Collegiate baseball players with more optimal functional movement patterns demonstrate better athletic performance in speed and agility. Issue 5 (4th March 2019) - Liang, Yu-Pin; Kuo, Yi-Liang; Hsu, Hsiang-Chin; Hsia, Yen-Ysung; Hsu, Ya-Wen; Tsai, Yi-Ju
ABSTRACT: Sports injuries are common among baseball players and may result in abnormal movement patterns, increased risks of future injury, and unsatisfactory performance. The Functional Movement Screen (FMS™) has been developed to detect abnormal functional movement patterns and can be used for predicting risks of sports injury. However, whether FMS™ scores are associated with athletic performance remains unclear. The goal of this study was to determine the association between functional movements and athletic performance in elite baseball players. Core stability, muscular strength and flexibility of the lower extremities, and FMS™, as well as athletic performance in sprinting, agility, and balance tests were assessed in 52 male collegiate Division I baseball players placed into two groups based on FMS™ scores. The high-scoring group demonstrated better athletic performance than the low-scoring group, with a shorter duration of the agility test. No group differences were found in core stability, muscular strength, or muscle flexibility, except for rectus femoris flexibility. Thus, the FMS™ score is associated with sprinting and agility performance in elite baseball players. These findings indicate that the FMS™ may have a role in predicting athletic performance and thereby help determine the goals of training regimens or return-to-play strategies.